Improving the creative thinking and collaborative skills of prospective biology teachers using the EMKONTAN learning model in environmental science courses - N. Nurwidodo; I. Ibrohim; S. Sueb; Fadhlan Muchlas Abrori; Tubagus Ahmad Darojat (University of Muhammadiyah Malang, 2023)
The implementation of the Environmental Science learning process so far has shown a lack of encouragement to improve students' 4C skills. The EMKONTAN learning model is one of the models that is believed to improve students' creativity, collaboration skills, and environmental literacy. This study aims to analyze the effectiveness of the EMKONTAN learning model in improving critical thinking and collaborative skills for prospective biology teacher students. EMKONTAN is a student-centered learning model (students’ active learning), oriented to creative learning, problem-based learning, collaborative learning, and provides opportunities for students to improve environmental learning. This research was conducted in the event semester of the 2020/2021 academic year at IKIP Budi Utomo Malang and FTTE Universitas Muhammadiyah Malang-Indonesia, involving 150 second-semester students through total sampling. Data was obtained through observation, questionnaires, and tests. The research used a pretest-posttest non-equivalent control group design. Data collection in this study was carried out using Google Forms, Google Classroom, Google Meet, and WhatsApp. Data analysis using statistical product and service solutions (SPSS) version 23 software. The analysis of covariance (ANCOVA) analysis results showed that EMKONTAN, PBL affected students' creativity and collaboration skills in biology teacher candidate students with a value of p<0.005. The least significant difference (LSD) result was significantly different in improving students' creativities thinking, and collaboration skills. The EMKONTAN class gained the highest post-test score. Therefore, EMKONTAN could be applicable to improve students' creative thinking and collaborative skills outcomes in environmental learning.